Advances in ethological approaches to explore rodent vocal communication - Abud, Ali; Wang, Yihan; Hafter, Rechuma; Tavakoli, Ehsan; Wu, Christina; Atapattu, Senadee; Raza, Ahmed; Ali, Mohammad; Al-Hadi, Ali; Khalid, Hamza; Sukhija, Rehmat K.; Stoodley, Tobias; et al. (Frontiers in Ethology, 2025)
Vocal communication is widespread across animals, from mammals to amphibians. In recent years, rodents have become an increasingly valuable group in which to study vocal communication. Rodents offer rich opportunities to examine vocalizations from proximate and ultimate ethological perspectives. Here, we identify recent advances in ethological research on rodent vocal communication by synthesizing contemporary studies from the past decade. We carried out a scoping review of research published between 2014 and 2024. This review involved a broad search for peer-reviewed primary research studies in APA PsycINFO, Embase, MEDLINE, PubMed, Scopus, and Web of Science databases. The search yielded 403 eligible studies on rodent vocalizations. We extracted information about the ethological perspectives, species, research environment, and animal sex and age groups. We also identified studies that focused on method development. We found that rodent vocal communication studies varied across ethological perspectives, with more studies carried out on vocal mechanisms and adaptive functions than on development and evolution. These studies covered a broad range of 88 rodent species, with high species diversity in function and evolution studies and low species diversity in mechanism studies. Artificial environments were used more often than naturalistic environments, especially in mechanism and development studies. Naturalistic environments were common in function and evolution studies. Adult males were used more often than any other sex and age groups. The use of age groups, but not sexes, varied across ethological perspectives. Together, these findings highlight several advantages of contemporary rodent research, including opportunities to carry out in-depth studies of vocal mechanisms and to compare diverse species. Based on these findings, we also identify potential areas for future research. These research areas include non-mechanistic questions, as well as expanding species diversity, research environments, and animal sex and age groups. Rodent research from multiple ethological perspectives will be crucial for building a comprehensive understanding of animal acoustic communication.